Investigating The Impact of Instructional Videos on Fostering EFL Learners' Semantic Perception: Case of Fellak Allaoua Middle School Berhoum, M'sila - Soumia Zoubiri; Lamia Helali (UNIVERSITY OF MOHAMED BOUDIAF- M’SILA, 2025)
Abstract This study investigates the washback effects of BEM (Brevet d'Enseignement Moyen) tests on middle school English as a Foreign Language (EFL) learners' choice of learning strategies in M’sila, Algeria. Given the high-stakes nature of the BEM examination, the research explores how these assessments influence student behaviors, particularly their reliance on specific learning strategies, such as rote memorization and test-oriented preparation, potentially at the expense of communicative and interactive language skills. The study employs a mixed-methods approach, combining quantitative questionnaires with qualitative interviews and classroom observations to assess both learners' and teachers' perspectives. Findings indicate a strong washback effect, where test format and perceived importance shape classroom instruction and learners' strategy preferences. The study concludes with pedagogical recommendations to align assessment with effective language learning practices, promoting strategies that support long-term language development rather than short-term test performance.
Keywords: Keywords: washback effect; Midel School EFL learners; Learning Stratigies.